Search for triple Higgs boson production in the 6b final state using pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Backes, Mathias; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Rassloff, Damir Fabrice; Sanfilippo, Lorenzo; et al. (Physical review, 2025)
A search for the production of three Higgs bosons (𝐻⁡𝐻⁡𝐻) in the 𝑏⁢¯𝑏⁢𝑏⁢¯𝑏⁢𝑏⁢¯𝑏 final state is presented. The search uses 126 fb−1 of proton-proton collision data at √𝑠 =13 TeV collected with the ATLAS detector at the Large Hadron Collider. The analysis targets both nonresonant and resonant production of 𝐻⁡𝐻⁡𝐻. The resonant interpretations primarily consider a cascade decay topology of 𝑋 →𝑆⁢𝐻 →𝐻⁡𝐻⁡𝐻 with masses of the new scalars 𝑋 and 𝑆 up to 1.5 and 1 TeV, respectively. In addition to scenarios where 𝑆 is off-shell, the nonresonant interpretation includes a search for Standard Model 𝐻⁡𝐻⁡𝐻 production, with limits on the trilinear and quartic Higgs self-coupling set. No evidence for 𝐻⁡𝐻⁡𝐻 production is observed. An upper limit of 59 fb is set, at the 95% confidence level, on the cross section for Standard Model 𝐻⁡𝐻⁡𝐻 production.
The ATLAS Collaboration: G. Aad, A. Ackermann, M. Backes, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, D.F. Rassloff, L. Sanfilippo, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser und weitere 2856
Gesehen am 17.10.2025